Spatio-temporal dynamics in the mixed fractional nonlinear Schrödinger equation - Aceves, Alejandro; Copeland, Austin (Frontiers in Photonics, 2022)
The effective engineering of linear and nonlinear optical properties in photonic media has led to new advances in the theory and applications of spatio-temporal light-matter interactions. In some instances research has been motivated by phenomena in a Quantum-Mechanical framework; two notable examples being Anderson localization and Parity-Time symmetry. Here we present theoretical and numerical results on light propagation in the presence of fractional diffraction and classical dispersion highlighting the role mixed-factionality has on stability, spatio-temporal localization and possible collapse events.